Digitization: its contribution to business management development - González Arencibia, Mario (2014)
This paper presents the main trends and discussions regarding the world ofones and zeros, with the understanding that many of the points addressedcould be subject to a detailed analysis. Based on the above, the objective of this paper is to promote critical reflection on the possibilities offered bydigitization for business management development. Results obtained indicatethat digitization, being a basis for innovative cultural practices, has becomea key strategic factor for business management competitiveness. This isdetermined due to its relevance in the production processes or new products,the competitor’s structure, the company’s competitive positions, as well asits organizational structure, human resources, and communications methods.